1971
DOI: 10.1152/ajplegacy.1971.220.5.1509
|View full text |Cite
|
Sign up to set email alerts
|

Calcium absorption and calcium-binding protein in chicks on differing calcium and phosphorus intakes

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

1973
1973
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(64 citation statements)
references
References 0 publications
4
60
0
Order By: Relevance
“…In an in-vitro trial, using ligated duodenal loops, Morrissey & Wasserman (1971) observed that broiler chicks absorbed a higher percent of a labeled 47 Ca (ranging from 70 to 90%) when diets low in Ca (0.08%) were fed for eight d prior to intestinal sampling regardless of dietary P levels, or when low P (0.25%) diets were fed regardless of dietary Ca levels. Chickens receiving a diet with normal P (0.65%) and normal Ca (1.20%) absorbed less than 50% of 47 Ca.…”
Section: Early Dietary Adaptationmentioning
confidence: 99%
“…In an in-vitro trial, using ligated duodenal loops, Morrissey & Wasserman (1971) observed that broiler chicks absorbed a higher percent of a labeled 47 Ca (ranging from 70 to 90%) when diets low in Ca (0.08%) were fed for eight d prior to intestinal sampling regardless of dietary P levels, or when low P (0.25%) diets were fed regardless of dietary Ca levels. Chickens receiving a diet with normal P (0.65%) and normal Ca (1.20%) absorbed less than 50% of 47 Ca.…”
Section: Early Dietary Adaptationmentioning
confidence: 99%
“…Ca absorption was estimated by an already described modification (Bonjour et al 1973a) of the in situ ligated loop method (Wasserman, 1963;Morrissey & Wasserman, 1971). The animals were anaesthetized with an i.P.…”
Section: Measurement Of Ca Absorptionmentioning
confidence: 99%
“…Further, animals fed diets deficient in calcium or phosphorus adapt to these deficiencies by an increase in the synthesis of 1,25(0H)2D3 (17)(18)(19)(20)(21), resulting in an increase in the efficiency of calcium and phosphorus absorption. These adaptations are associated with an increased synthesis of calbindin-D and its mRNA (17)(18)(19)(20)(22)(23)(24)(25)(26)(27)(28) …”
Section: Introductionmentioning
confidence: 99%